Alternative dispute resolution in business - Ponte, Lucille M.
ALTERNATIVE DISPUTE RESOLUTION IN BUSINESS provides an overview of innovative ADR methods that have been implemented to deal with domestic and international business disputes. This text takes a managerial approach that provides information on various aspects of ADR - such as negotiation, mediation, arbitration - to help managers make educated decisions when faced with choices of trial or ADR